2013
DOI: 10.3233/wor-2012-01564
|View full text |Cite
|
Sign up to set email alerts
|

The influence of work-life balance, choice and a meaningful location on work transitions

Abstract: Objective: To explore career transitions using an occupational perspective. Participant: One man shared his views on career transitions to elaborate concepts on work-life balance, choice and meaning. Method: Narrative reflection and theoretical exploration of occupational concepts underscoring career transitions. Results: Three concepts are important to understanding career transitions, work-life balance, making meaning choices, and place. Conclusions: Further development in work transitions can be elaborated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Everyday, individuals engage in many divergent roles that come with different responsibilities and challenges, which can lead to work–life conflict (Cheng and McCarthy, 2013). Work–life conflict does not have to be about one having supremacy over the other; work–life conflict can be about how work and non-work responsibilities can coexist in harmony (Lisson et al , 2013). As Foy (2015) and others (Jang et al , 2011; Murphy and Doherty, 2011) have noted, the relationship between work and life is, for example: family friendly; balanced; conflicted; and flexible.…”
Section: Work–life Conflictmentioning
confidence: 99%
“…Everyday, individuals engage in many divergent roles that come with different responsibilities and challenges, which can lead to work–life conflict (Cheng and McCarthy, 2013). Work–life conflict does not have to be about one having supremacy over the other; work–life conflict can be about how work and non-work responsibilities can coexist in harmony (Lisson et al , 2013). As Foy (2015) and others (Jang et al , 2011; Murphy and Doherty, 2011) have noted, the relationship between work and life is, for example: family friendly; balanced; conflicted; and flexible.…”
Section: Work–life Conflictmentioning
confidence: 99%
“…Work–life balance policies were one of PC's constructs, which is very important for the organization (Freese et al , 2008). Past studies showcase the relationship between work–life balance and organizational outcomes (Armstrong et al , 2015; Beutell et al , 2019; Lisson et al , 2013). Thus, this caters to the balanced situation where explorative and exploitative activities were present (with the help of work–life balance work practices).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to a study conducted by Longo , which found that nurses (including F‐LNMs) demonstrated caring behaviours towards their colleagues by coming to know them on both a professional and a personal level. The concept of work‐life balance is about achieving a state of equilibrium between the demands of work and home life . A vast body of literatures has documented the issue of work‐life balance , which indicates the importance of balance between people's professional and personal lives.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of work‐life balance is about achieving a state of equilibrium between the demands of work and home life . A vast body of literatures has documented the issue of work‐life balance , which indicates the importance of balance between people's professional and personal lives. Striking balance between work and life is the foundation of wellbeing and incorporates elements such as developing and maintaining good physical health and fitness, maintaining an appropriate level of energy and vitality, enjoying emotional and psychological stability, engaging in harmonious relationships and developing effective stress management strategies and coping skills .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation